Characterization of Quorum Sensing and Quorum Quenching Soil Bacteria Isolated from Malaysian Tropical Montane Forest - Kok-Gan Chan; Wai-Fong Yin; Yeun-Mun Choo; Choon-Kook Sam; Teik-Min Chong; Chong-Lek Koh (Sensors, 2012)
We report the production and degradation of quorum sensing N-acyl-homoserine lactones by bacteria isolated from Malaysian montane forest soil. Phylogenetic analysis indicated that these isolates clustered closely to the genera of Arthrobacter, Bacillus and Pseudomonas. Quorum quenching activity was detected in six isolates of these three genera by using a series of bioassays and rapid resolution liquid chromatography analysis. Biosensor screening and high resolution liquid chromatography-mass spectrometry analysis revealed the production of N-dodecanoyl-L-homoserine lactone (C12-HSL) by Pseudomonas frederiksbergensis (isolate BT9). In addition to degradation of a wide range of N-acyl-homoserine lactones, Arthrobacter and Pseudomonas spp. also degraded p-coumaroyl-homoserine lactone. To the best of our knowledge, this is the first documentation of Arthrobacter and Pseudomonas spp. capable of degrading p-coumaroyl-homoserine lactone and the production of C12-HSL by P. frederiksbergensis.